2022
DOI: 10.1177/00494755221074754
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of sexual transfer of mycobacteria from male to female partners reporting to an IVF clinic

Abstract: Female genital tuberculosis (GTB) contributes significantly to infertility in low- and middle-income countries. Dissemination of infection from pulmonary and extrapulmonary sites is the major reason for causation of GTB. Additionally, sexual transmission of GTB from male partners has been reported. We selected 81 couples desiring babies from an in vitro fertilization clinic. We used multiplex-PCR for mycobacterial detection in semen of males, in the endometrium of their female counterparts and in the products … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…10 Sexual exposure is also related to GUTB risk, if mTB is detected in semen. 11 Two main mechanisms though have been suggested: either haematogenous spread from the pulmonary focus or local infection arising from the seminal vesicles or prostate via retrograde ejaculation. 12 TTB is a diagnostic challenge and is difficult to diagnose based on imaging characteristics and clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…10 Sexual exposure is also related to GUTB risk, if mTB is detected in semen. 11 Two main mechanisms though have been suggested: either haematogenous spread from the pulmonary focus or local infection arising from the seminal vesicles or prostate via retrograde ejaculation. 12 TTB is a diagnostic challenge and is difficult to diagnose based on imaging characteristics and clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of the genital tract is mostly secondarily from a focus elsewhere; haematogenous dissemination, lymphatic spread or direct spread from adjacent abdominal organs have all been implicated. In addition, some evidence to suggest that FGTB can be acquired as primary infection via sexual transmission also exists, although data are limited [6 ▪▪ ]. Case studies have yielded molecularly identical strains of MTB from sexual partners affected by genitourinary TB, supporting the plausibility of sexual acquisition of MTB infection [7].…”
Section: Epidemiologymentioning
confidence: 99%
“…This study also reported that the sperm quality or motility was not a factor in the failure of pregnancy. 31…”
Section: Known Transmission Routes and Evidence Of Sexual Transfermentioning
confidence: 99%
“…30 A multiplex PCR-based study carried out by Datta et al in 2022 at the Calcutta Fertility Mission reported 165 couples with primary and secondary infertility between 2019 and 2020. 31 In this study design, the couples with known causes of infertility such as tubal factors (22 pairs), endometriosis (17), Polycystic Ovarian Disease (14), Pelvic Inflammatory Disease (11), Hormonal imbalance (10), history of pulmonary or EPTB (6), history of Azoospermia (2), and local bacterial infection in genitalia (2) were screened and excluded. The remaining 81 sexually active couples with unknown causes of infertility, normal functioning fallopian tube and hormonal profile, and absence of any local bacterial infection were included.…”
Section: Known Transmission Routes and Evidence Of Sexual Transfermentioning
confidence: 99%